Photoresponse and electrical characterization of photodiode based nanofibers ZnO and Si - Yakuphanoğlu, Fahrettin; Farooq, W. Aslam (Elsevier Sci Ltd, 2011)
Zinc oxide semiconductor is a promising material for various optoelectronic applications such as visible light and UV detectors. The photoresponse and electrical characterization of the photodiode based nanofibers n-ZnO and p-Si semiconductors have been investigated. The Al/p-Si/n-ZnO/AI diode shows a clear rectifying behavior with a rectification ratio of 2.90 x 10(4) at +/- 4 V. The diode exhibits a photoconducting behavior with a ratio I(on/off) of 60. The photoconducting mechanism of the diode is controlled by the presence of exponential distribution of impurity levels in the forbidden band of ZnO. The obtained results indicate that the Al/p-Si/n-ZnO/AI diode can be used as photodiode in optoelectronic applications. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: ZnO; Sol gel; Nanoparticles; Photodiode